European Pediatric Surgeons' Association Survey on Timing of Inguinal Hernia Repair in Premature Infants - Soyer, Tutku; Pio, Luca; Gorter, Ramon; Martinez, Leopoldo; Dingemann, Jens; Pederiva, Federica; Dariel, Anne; Zani-Ruttenstock, Elke; Kakar, Mohit; Hall, Nigel J. (European Journal of Pediatric Surgery, 2024)
Aim This article evaluates the practice patterns of European Pediatric Surgeons' Association (EUPSA) members regarding the timing of inguinal hernia (IH) repair in premature infants.Methods Online survey containing 29 questions distributed to EUPSA members during January 2023.Results A total of 180 responds were received. Overall, IH repair prior to discharge was favored by 60% of respondents when there was a history of incarceration and 56% when there was not. In the case of very/extremely premature infants (< 32 weeks) with no history of incarceration, fewer (43%) respondents postpone the surgery until after discharge. The majority of respondents cited the risk of incarceration as the reason for advocating surgery prior to discharge, whereas a reduced risk of apnea was the most cited reason for respondents who prefer delayed surgery. Open approach under general anesthesia was favored by 54% of respondents, with 27% of them preferring open approach with spinal anesthesia. Laparoscopic surgery for premature infants is used in 11% while 7% of them preferred in all premature infants including extremely/very premature ones. Contralateral side evaluation was never done by 40% of respondents and 29% only performed it only during laparoscopic repair. The majority of respondents (77%) indicated that they have an overnight stay policy for premature infants < 45 weeks of gestation.Conclusion There is variation in the practice patterns of pediatric surgeons in the treatment of IH in premature infants. Due to the concern for the high risk of incarceration, IH repair before discharge was the most prevalent practice. Lower risk of postoperative apnea was cited as the most common reason for delaying surgery. Randomized studies are required to establish the optimal timing for IH repair in premature infants.
Keywords: premature; infants; inguinal hernia; pediatric surgery